(untitled) (Indonesian Contemporary Nursing Journal (ICON Journal), 2023)
Aims: To analyze the potential of honey hydrogel modern dressing in wound healing process in patients with grade II diabetic ulcers. Methods: The research design used a true experiment with a randomized pretest posttest control group design. This study had 36 respondents who were divided into 2 groups through simple random sampling. The intervention group was given honey hydrogel with 4 measurements. The first measurement or pretest on day 1, the second measurement or posttest 1 on day 7, the third measurement or posttest 2 on day 14, and the fourth measurement or posttest 3 on day 21. The instrument used to measure patient wound healing using the Bates-Jensen Wound Assessment Tool (BWAT). Results: The increase in the mean wound healing score of patients who were given honey hydrogel modern dressing from a score of 42.11 on day 1 to 34.56 on day 21 with p = 0.001 while the increase in the mean wound healing score of patients who were given manufacturer hydrogel modern dressing from a score of 41.67 on day 1 to 37.17 on day 21 with p = 0.001. The effect size between the intervention group and the control group is quite strong with a value of 0.78. Conclusion: Honey hydrogel has the potential to promote wound healing in patients with grade II diabetic ulcers. Further research is recommended to explore the use of honey hydrogel by innovating the manufacturing process to ensure consistent dosing in the treatment of grade II diabetic ulcers.